Extracellular nicotinamide phosphoribosyltransferase: role in disease pathophysiology and as a biomarker - Semerena, Elise; Nencioni, Alessio; Masternak, Krzysztof (Frontiers in Immunology, 2023)
Nicotinamide phosphoribosyltransferase (NAMPT) plays a central role in mammalian cell metabolism by contributing to nicotinamide adenine dinucleotide biosynthesis. However, NAMPT activity is not limited to the intracellular compartment, as once secreted, the protein accomplishes diverse functions in the extracellular space. Extracellular NAMPT (eNAMPT, also called visfatin or pre-B-cell colony enhancing factor) has been shown to possess adipocytokine, pro-inflammatory, and pro-angiogenic activities. Numerous studies have reported the association between elevated levels of circulating eNAMPT and various inflammatory and metabolic disorders such as obesity, diabetes, atherosclerosis, arthritis, inflammatory bowel disease, lung injury and cancer. In this review, we summarize the current state of knowledge on eNAMPT biology, proposed roles in disease pathogenesis, and its potential as a disease biomarker. We also briefly discuss the emerging therapeutic approaches for eNAMPT inhibition.